Pretreaments Used for Fruit Biomass Peel Residue to Yield Ethanol Production - Lalitha, G. (Recent Research in Science and Technology, 2011)
The present study was carried out with the objective of determining the optimal pretreatment conditions for high efficiency ethanol production from the fruit biomass peel residue. The residue was subjected to alkaline hydrogen peroxide pretreatments and sulfuric acid pretreatments, followed by three weeks of fermentation using the Fusarium solani, the pre-treatment process effectively removed lignin. Ethanol production in the culture sample was monitored using high performance liquid chromatography. With Alkaline treatment 2% H2O2 at pH 13 soaked for 8hrs removed 45%, ethanol produced was found to be 115 mg/L. With Acid treatment 0.2mol/L H2SO4 fermenting for 15 days ethanol produced 12g/L of ethanol in 24hr. This preliminary study showed that ethanol production from fruit biomass peel residue is possible. A significant removal lignin from the fruit biomass peel residue, which resulted in higher production of ethanol, can be made from the fruit biomass peel residue. The fermentation system needs to be optimized further to scale up the process for large-scale production.